PRINSIP ANALOGI PADA KATA LARANGAN DI MEDIA SOSIAL (STUDI ANALISIS WACANA KRITIS) - Lestari, Laila Tri; Mualifah, Siti (LPPM UNISDA, 2024)
This study aims to analyze discourse on internet media using the principle of analogy. This type of research with a qualitative descriptive method. The data source for this research is the internet media. The technique used data recording techniques. This technique determines the analysis of the description and conclusion of the data. The results of the research based on the prohibition discourse that exists around the community require the principle of analogy in determining the purpose of the information conveyed in the discourse. So that there is no misinterpretation of the sentence that is read. The results of the research analysis show that there are four places where there is a prohibition discourse, these places are schools, shops, hospitals and roads. Based on the results of the study, it was found that there are five prohibition discourses in schools. The discourse in the store contains five prohibition discourses. Discourse in the hospital there are five discourses of prohibition. The discourse on the street contains seven prohibition discourses.